TINGKAT KETERAMPILAN DASAR BERMAIN FUTSAL SISWA PESERTA EKSTRAKURIKULER SMA NEGERI 1 KUTAPANJANG - Musran, Musran; Prabowo, Riski Ari Prabowo Ari; Kurniawan, Erizal; Syahrianursaifi, Syahrianursaifi (Jurnal Dedikasi Pendidikan, 2022)
The purpose of this study was to determine the level of basic skills of playing futsal for students participating in extracurricular futsal at State Senior High School 1 Kutapanjang. This research is a descriptive type of research that uses a qualitative approach method. The population and sample in this study were 25 students participating in extracurricular futsal at State 1 Kutapanjang High School, with saturated sampling technique. Data collection was carried out with the Futsal Basic Skills Test aged 16-22 years. includes: dribling, stop passing, and shooting. The results of the research obtained are the basic skills of playing futsal for students participating in extracurricular futsal at the State Senior High School 1 Kutapanjang as follows: 1) good category with a frequency of 10 students (40.00%), 3) sufficient category with a frequency of 7 students (28.00%), and 4) less category with a frequency of 8 students (32.00%). The research conclusion is that the level of basic skills in playing futsal for students participating in extracurricular futsal at State 1 Kutapanjang High School is categorized as good